Membangun Generasi Wirausaha: Pelatihan Kewirausahaan untuk Pelajar di SMA Negeri 1 Karanganyar Kebumen - Lina, Roidah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Entrepreneurship is an important factor in economic development. The younger generation, especially students, have great potential to become entrepreneurs. However, they often do not have sufficient knowledge and skills to start a business. Therefore, efforts need to be made to build a generation of entrepreneurs through entrepreneurship training. The aim of this community service activity is to increase entrepreneurial knowledge and skills for students at SMA Negeri 1 Karanganyar Kebumen. This community service activity is carried out using lecture, discussion and practical methods. This community service activity has succeeded in increasing students' entrepreneurial knowledge and skills. Training participants admitted that they were more motivated to start a business after attending this training.